Diaspora networks in international marketing: how do ethnic products diffuse to foreign markets? - Elo, Maria (2021)
While diaspora networks can be instrumental for diffusion, their 'all-in-one' role has remained underexplored in international marketing management literature. Diaspora actors function as part of the channel system, diffusing ethnic products and creating the 'highway' to new markets. Globalisation has increased geographic dispersion and plurality, fostering their participation in international business as connectors. To this end, exporting firms benefit from diaspora resources while co-creating participant distribution. This mechanism - the 'invisible diaspora hand' - shapes the internationalisation processes of products and ethnic value creation on behalf of the firm. This study examines how ethnic products diffuse across borders, and how diaspora networks participate in the international diffusion and ethnic crossover process by orchestrating resources across contexts and networks. The findings contribute to advancing our understanding of product diffusion and mainstreaming, and theorising on the role of transnational diaspora in international market entry, product diffusion and international marketing.